Kepuasan Konsumen Ditinjau Dari Kualitas Pelayanan Dan Fasilitas Pada RSU RA. Kartini Jepara Tahun 2015 - Erina, Lisa; , Dr. H. Sabar Narimo, M.M., M.Pd (2015)
The purpose of this study was to determine 1) the effect of service quality on customer satisfaction, 2) the effect of the facility to customer satisfaction, 3) influence the quality of services and facilities to customer satisfaction. The method used is associative study with a quantitative approach. The technique of collecting data using questionnaires. This research was carried out at RSU RA. Kartini Jepara in April with a population of 229. Before the instrument is used, first conducted trials (try out) instrument. Instruments tested to the patient or the patient's family waited outside the population residing in the sample. Samples were taken based on the tables Isaac and Michael with a level of 95% which is a number of 140 patients or relatives of patients who waited with incidental sampling technique. The conclusion of this study were 1) the quality of service a positive effect on customer satisfaction. It is based on multiple linear regression analysis obtained t> t table, namely 6.468> 1.977 and the significance value <0.05 is 0.000 with the relative contribution of 79.37% and 24.44% effective contribution, 2) facility has positive effect on customer satisfaction. It is based on multiple linear regression analysis obtained t> t table, namely 2.799> 1.977 and the significance value <0.05 is 0.006 with the relative contribution of 20.53% and the effective contribution of 6.32%, 3) quality of services and facilities positive effect on consumer satisfaction. This is evidenced by Fhitung = 30.420> Ftabel = 3.06 and a significance value <0.05 is 0.000. The result of the coefficient of determination (R2) of 0.308 obtained mean pngaruh provided by a combination of a variable quality of service and facilities to customer satisfaction is at 30.8% while the remaining 69.2% is influenced by other variables not examined. Keywords: quality of service, facilities, consumer satisfaction